2007
DOI: 10.1111/j.1471-0528.2007.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes and antiretroviral treatment in a national cohort of pregnant women with HIV: overall rates and differences according to nationality

Abstract: We used data from the main surveillance study of HIV and pregnancy in Italy to evaluate possible differences in pregnancy care and outcomes according to nationality. Among 960 women followed in 2001-06, 33.5% were of foreign nationality, mostly from African countries. Foreign women had lower rates of preconception counselling and planning of pregnancy. They had more frequently HIV diagnosed during pregnancy, with a later start of antiretroviral treatment and lower treatment rates at all trimesters but not when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Any changes to treatment should be made swiftly to avoid switching ART during or close to the start of pregnancy. Given the probable high number of unplanned pregnancies in this population [15,16,17], it is important that clinicians prescribing ART consider whether women of childbearing age might become pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…Any changes to treatment should be made swiftly to avoid switching ART during or close to the start of pregnancy. Given the probable high number of unplanned pregnancies in this population [15,16,17], it is important that clinicians prescribing ART consider whether women of childbearing age might become pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the international Antiretroviral Pregnancy Registry (APR) (11) and cohort studies (12, 13) have found no evidence of increased prevalence of overall congenital abnormalities after first-trimester EFV exposure (2.8/100 live births), compared to second or third-trimester EFV exposure (3.6/100 live births), to first-trimester NVP exposure (2.1/100 live births) or to the general population (2.7/100 live births). Detailed data on these pregnancy outcomes with a breakdown by miscarriage, preterm delivery (PTD), stillbirth and low birth weight (LBW) are hardly reported (10, 12, 14, 15). Our objective was to describe and compare the pregnancy outcomes between women who were exposed to EFV and those exposed to NVP during the first trimester in Côte d’Ivoire, West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about rates of unintended pregnancy and choice of contraception among HIV-infected women in Ukraine. Some Western European studies have indicated that around half (51–58%) of pregnancies among HIV-infected women are unintended (Fiore et al ., 2006; Floridia et al ., 2007), whereas in one Russian survey of HIV-positive women, 54% of those who had recently completed their pregnancy reported not having planned their pregnancy (Vartapetova et al ., 2006). …”
Section: Introductionmentioning
confidence: 99%